PENGARUH PENGGUNAAN MEDIA DAN EFEK PESAN PADA AKUN INSTAGRAM PLATFORM PSIKOLOGI ONLINE @RILIV TERHADAP KEPUASAN FOLLOWERS - Ghina Farhany (2022)
The purpose of this study was to examine the effect of media usage and the message effects on the Instagram account of the online psychology platform @Riliv on followers' satisfaction. The background of this research is that the researcher wants to know how much influence the use of media and the effect of messages on the @Riliv Instagram account on followers' satisfaction. The theory used to explain this research is Uses and Gratifications theory. This study uses an associative quantitative approach with a survey method in the form of a Google Form questionnaire distributed to 100 respondents who follow the @Riliv Instagram account. The sampling technique used is the Non-Probability Sampling technique (Purposive Sampling). This study took data sources from primary data and secondary data. The data analysis technique used is descriptive statistics. Through the results of hypothesis testing with the F test (ANOVA), it was found that the calculated F value of 86.992 is greater than the F table value of 3.09, it can be interpreted that there is an influence between the variable of media usage and the message effects variable on the @Riliv Instagram account on followers' satisfaction variable. Based on the results of the determination test, it was also found that the magnitude of the influence of media use and the message effects on the @Riliv Instagram account on followers' satisfaction was 64.2%. These results indicate that the use of media and the effect of messages on the @Riliv Instagram account has a fairly important role in fulfilling desires or giving satisfaction to followers.